Analisis Perbandingan Model Altman, Springate, Zmijewski, Dan Grover Dalam Memprediksi Kebangkrutan Perusahaan Di Bursa Efek Indonesia (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2017) - Anton Robiansyah; Yusmaniarti Yusmaniarti; Iwi Karmita Sari; Herry Novrianda; Tito Irwanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study compares the feasibility of the Bankruptcy prediction model if used to predict manufacturing companies. The test in this study is logistic regression. The sample in this study consisted of 79 manufacturing companies listed on the Indonesia Stock Exchange from 2012-2017 with a purposive sampling method. This research is quantitative research where the analytical tool used is logistic regression test with SPSS version 18. The study results indicate that of the four models studied. The Springate model cannot predict the bankruptcy of manufacturing companies listed on the Indonesia Stock Exchange because it has a significant value of 0.175 > 0.05. This study also indicates that the Altman model is the most appropriate for predicting the bankruptcy of manufacturing companies compared to Springate, Zmijewski, and Grover.